THE RELATIONSHIP OF EMPLOYEE EMPOWERMENT AND EMPLOYEE ENGAGEMENT: THE ROLE OF FLEXIBLE WORK ARRANGEMENTS AND CAREER DEVELOPMENT AS STIMULANTS - Setiyawami, Setiyawami; Waliah, Siti; Sriharyati, Santy; Oktisari, Dwi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
AbstractIn the creative industry, the relationship between employee empowerment and employee engagement has a very important role. Employees who feel empowered to contribute with creative ideas and participate in the decision-making process will feel more connected to the company's vision and values. The main aim of the research is to analyze the influence of employee empowerment, flexible work arrangements, and career development on employee engagement. The sample in this research consisted of 190 employees who worked in the creative industries in Indonesia who were determined using a convenience sampling approach. Data collection uses a questionnaire instrument which is then distributed online. Data analysis uses the SPSS application by displaying the results of data processing through validity and reliability tests, multiple regression analysis, coefficient of determination, and hypothesis testing. Based on the results of data analysis, it is stated that employee empowerment, flexible work arrangements, and career development have a positive and significant effect on employee engagement. The theoretical implications of the research explain that implementing policies and practices that support employees in terms of work flexibility and career development can significantly increase employee engagement and performance. Meanwhile, practically, organizations in the creative industries need to pay attention to the importance of creating a work environment that supports employee flexibility and career growth. This can be done through implementing policies that allow remote work, flexible work schedules, and support for skills and career development